Just seem to be struggling to understand what I am missing here?

I have;

x - 8 =3x + 20

7

This is what I have done to try and find the value for x

7(x - 8) = 7(3x + 20)

7

56 - 7x = 3x + 20

-7x -3x = 20 - 56

-10x=-36

-10 -10

x = 3.6

Substitute value into x

3.6 - 8 =3 x 3.6 + 20

7

-4.4 = 4.4

My problem to me is that -4.4 is not equal to 4.4?

The equation should not have two routes?

Please advise if there is an alterative technique to solve this type of problem?

P.S. the 7 above (denominator) should be divided by the numberators on the RHS of the equals sign. This software program seens to move the integer to the LHS